Ovalbumin causes impairment of preimplantation embryonic growth in asthma-induced mice. (February 2021) - Wafriy, Che Ismail; Kamsani, Yuhaniza Shafinie; Nor-Ashikin, Mohamed Noor Khan; Nasir, Nurul Alimah Abdul; Hanafiah, Mohammad
Highlights: 10 μg/200 μL of ovalbumin (OVA) reduced the number of preimplantation embryos at each developmental stage. 10 μg/200 μL of OVA impaired morphology of preimplantation embryos at each developmental stage. The effects of 10 μg/200 μL OVA were insignificant in maternal serum. Further studies on different ovalbumin concentrations are needed. Abstract: Insufficient experimental studies have reported the effect of ovalbumin (OVA) as an allergen towards embryonic growth in asthma mouse model. The impact of 10 μg/200 μL OVA on maternal inflammatory and oxidative stress (OS) responses, and preimplantation embryonic development was investigated in this study. We first established OVA-induced asthma mouse model, and following superovulation, mated the females and challenged them with Methacholine (Mch) test. Upon embryo retrieval, only those with the highest implantation potential were cultured in vitro. Significant reduction in the number of embryos at each preimplantation stage was noted in the treated group. Uneven sized blastomeres at 2-, 4- and 8-cell stages were also evident in this group. Embryo fragmentation was significant at only 2-, 4- and 8-cell stages. We also found that OVA tended to raise maternal inflammatory and OS biomarker levels as well as to cause inappropriate levels of pregnancy hormones progesterone (P4 ) and estrogen (E2 ) although insignificant. The combined results indicate that 10 μg/200 μL OVA had altered both quality and quantity of the embryos in asthma mouse model although its effect on pregnancy hormones, inflammatory and OS responses were non-pathological.